Identifying big data’s opportunities, challenges, and implications in finance - Sun, H.; Rabbani, M. R.; Sial, M. S.; Yu, S.; Filipe, J. A.; Cherian, J. (Mathematics, 2020)
One of the latest innovations in business and technology is the use of big data, as daily data is generated by billions of events. The big data issue is now considered in the accountants and finance professionals’ field as one of the most important sources for the analysis of financial products and services. This study is very innovative, aiming our research to identify the opportunities, challenges, and implications of big data in the finance area. It is our purpose to find competitive advantages in extents on which big data brings visible benefits, also pointing out the challenges that a company may face in this field, as are the cases of customers' data security or customer satisfaction processes. The identification of this kind of dynamics allows us to conclude about the big advantages of big data on these analyses and big data’s deep impact on finance. Very particularly, the big data is now commonly used by financial institutions and banks for analytical purposes in financial markets contexts. We have conducted an exploratory survey of the existing literature to highlight such connections. In the last part of our study, we also propose some directions for future research.